CHARACTERIZATION OF ATTENTION FEATURES IN THE PROCESS OF SPEECH DEVELOPMENT - Maxmudov Xurshid Shuxratovich; Solijonova Ruxshona Akmaljon qizi; Nuriddinova Mohinur Hamidullo qizi (Bright Mind Publishing, 2025)
This article is significant for its ideas that the attention mechanism is related to the reflex activity of the brain, that in this reflex, which is also innate for humans, attention depends on external stimuli, that the characteristics of attention are characterized in the process of speech development, and that it has a complex functional structure.
Keywords: Attention, speech development, involuntary, voluntary and post-voluntary attention, volume, stability, concentration, distribution.